O aleitamento materno de recém-nascidos prematuros após a alta hospitalar - Cynthia Marcia Romano Faria (2010)
The objective of this study is to analyze aspects related to breast-feeding of premature newly born babies after they leave the hospital, from the experience of the mother. To reach the goals proposed, a qualitative approach was used, taking the theoretical-methodological orientation from dialectic. The research took place in fourteen houses of newly born babies who received treatment in the Neonatal Intensive Care Unit of Sofia Feldman Hospital, in Belo Horizonte, Brazil. The mothers of these newly born babies were subjects of this research. The followingcriteria were used: Being in their houses for at least 30 days; having beenreleased from the exclusive breast-feeding after being in the NICU. Datacollection was done via interview with semi-structured scrip and via participant observation. The field diary was used as an instrument of the researcher. Data was analyzed using the Content Analysis technique and the Narrative was build to present the analysis of each case, revealing the uniqueness of each woman and her baby in the process of breast feeding. From the narrative, the following categories were revealed: The hospital as a learning environment; the home as a comfort and freedom environment; the social network as mediator of breast feeding at home; the necessary technology for the success of breast feeding; theneed of continued assistance to the newly born baby; the material conditions and breast- feeding. Data analysis allowed showing that breast-feeding of premature newly born babies is unique for each woman in their daily-lives. The social network worked as a mediator both encouraging and discouraging the continuity of the breast-feeding. The breast-feeding experience during the time at the hospital was identified as a possibility of learning with the health team. Therefore,it is considered the continuity of the assistance to the newly born baby in order to support the woman in the breast-feeding process. The results of this study allow the affirmation that breast-feeding is inserted in the context of the womans life. Ergo, it is necessary to develop an approach, by both public policies and health professionals, that contemplate aspects not only emotional, but also cultural, historical, and social, that are involved in this complex process.